PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Saskia Panjaitan; Herti Diana Hutapea; Bonifasius H. Tambunan (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the influence of the Independent Board od Commissioners, Board of Directors and Audit Committee on the financial performance od properties and real estate companies listed on the Indonesia Stock Exchange in 2022-2024. The research method used is a quantitative method with multiple linear regression analysis. The research sample uses a purposive sampling method consisting of 44 companies with a total of 132 data observations. The test results show that good corporate governance structure has no effect on financial performance. This indicates that financial performance is influenced by factors other than the research, such as macroeconomic factors, capital structure and company size. Keywords: Independent Board of Commissioners, Board od Directors, Audit Committee, Financial Performance.